Ritual Construction, Use and Retirement of Mimbres Three Circle Phase Great Kivas. Issue 3 (20th November 2015) - Creel, Darrell; Anyon, Roger; Roth, Barbara
Abstract : Three Circle phase great kivas in the Mimbres area of southwest New Mexico have been the subject of new field investigations and reanalysis of data from earlier excavations. The findings have led to an enhanced and more detailed understanding of physical changes in these special buildings during the Three Circle phase, particularly with regard to dating and ritual behaviors associated with construction, use, and formal retirement.